(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article addresses the requirements of professional and pedagogical training in higher education institutions for future students of bachelor and master degrees. Examples of graphic and technological pedagogical activity for educational, scientific, research, methodological, and spiritual educational work are given. Some examples of innovative activities in the training of former teachers of visual arts.